Aspects of socio-spatial unity of Kabarda and Balkaria in the materials of the newspaper "Kavkaz" - Yuzanna M. Azikova (Кавказология)
The article analyzes the depiction of the interactions between the populations of Kabarda and Balkaria in the newspaper “Kavkaz,” within the context of the socio-spatial framework of the Central Caucasus from the 19th to early 20th century. An examination of the authors' and editorial staff's interpretations of the relationship between Kabardians and Balkars, alongside the newspaper's portrayal of the Russian government's initiatives to establish a new administrative-territorial division of the Caucasus within its legal framework, was conducted. The study is based on a “narrative”, descriptive and explanatory approach, which allows avoiding subordination to a strictly defined concept and allows focusing on the analysis of source data and the consistent reconstruction of facts and all possible interactions in the case under study. The materials involved are analyzed based on historical-systemic method. The work shows the fundamental grounds for building Kabardino-Balkarian ties, as well as the nature of coverage of such an issue in the pages of the periodical press. The totality of the materials of the newspaper “Kavkaz” on the Kabardino-Balkarian unity allows us to see that its design corresponded to the internal logic of the relationship between continuity and metamorphosis of a deeply conditioned and historically established socio-territorial structure. Publications in the newspaper "Kavkaz" of government decisions on reforms in the Central Caucasus also show that the imperial authorities took into account the historical and cultural foundations and economic realities of building relationships between Kabardians and Balkars.